Overview of National Policy Contexts for Entrepreneurialism in Higher Education Institutions - Williams, Gareth (OECD Publishing, 2005)
This paper is based on seven national reports on national policies concerned with entrepreneurialism in universities as the context for a more detailed study of entrepreneurial behaviour in universities in the seven countries. It claims that the entrepreneurial university is a useful generic epithet to describe the manifold changes in mission, management and funding that many universities in Europe have experienced in the past two decades. The concept of university entrepreneurialism in most countries is linked to the "third mission" that is supplementing the long established teaching and academic research functions of universities and other higher education institutions. However, some governments are also concerned to encourage universities to embody the teaching of entrepreneurialism in at least some of their conventional courses. Five main drivers of entrepreneurial activities in the countries taking part in the "European Universities for Entrepreneurship: their role in the Europe of Knowledge", (EUEREK) study are identified: ideology; expansion in the number of institutions; the knowledge society; globalisation; financial stringency. In some countries, especially in Eastern Europe there has been rapid growth in numbers of private higher education institutions. There are questions about whether this is an indication of entrepreneurialism, or of lack of entrepreneurial dynamism in the established public universities .The paper concludes with a preliminary review of managerial and governance changes in universities and colleges accompanying the growth of entrepreneurial and third mission activities